Established and Emerging Regulatory Roles of Eukaryotic Translation Initiation Factor 5B (eIF5B) - Chukka, Prakash Amruth Raj; Wetmore, Stacey D.; Thakor, Nehal (Frontiers in Genetics, 2021)
Translational control (TC) is one the crucial steps that dictate gene expression and alter the outcome of physiological process like programmed cell death, metabolism, and proliferation in a eukaryotic cell. TC occurs mainly at the translation initiation stage. The initiation factor eIF5B tightly regulates global translation initiation and facilitates the expression of a subset of proteins involved in proliferation, inhibition of apoptosis, and immunosuppression under stress conditions. eIF5B enhances the expression of these survival proteins to allow cancer cells to metastasize and resist chemotherapy. Using eIF5B as a biomarker or drug target could help with diagnosis and improved prognosis, respectively. To achieve these goals, it is crucial to understand the role of eIF5B in translational regulation. This review recapitulates eIF5B’s regulatory roles in the translation initiation of viral mRNA as well as the cellular mRNAs in cancer and stressed eukaryotic cells.